2004
DOI: 10.1111/j.1756-1051.2004.tb00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal development of vegetation and geomorphology in a man‐made beach‐dune system by natural processes

Abstract: Vestergaard, P. 2006. Temporal development of vegetation and geomorphology in a man-made beach-dune system by natural processes. -Nord. J. Bot. 24: 309-326. Copenhagen. ISSN 0107-055X.Twenty-four yrs of primary succession in a man-made beach-dune system at the Baltic coast of Denmark, built of calcareous, marine sand and the dune planted with Ammophila arenaria, was studied by qualitative observations, quantitative records in permanent plots, levelling and soil analysis within a selected area of 0.75 ha. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…As previously demonstrated elsewhere, we found that marram grass (Ammophila arenaria) plantation combined with trampling protection is a very efficient method allowing sand accretion and dune building (Lillis et al, 2004;Vestergaard, 2004;Grafals-Soto, 2012). Although This positive effect of restoration on sand accumulation was followed by an increase in gamma species richness and by an increase in vegetation conservation status at the alpha (i.e.…”
Section: Positive Effect Of Restoration On Geomorphology Typical Spec...supporting
confidence: 63%
See 1 more Smart Citation
“…As previously demonstrated elsewhere, we found that marram grass (Ammophila arenaria) plantation combined with trampling protection is a very efficient method allowing sand accretion and dune building (Lillis et al, 2004;Vestergaard, 2004;Grafals-Soto, 2012). Although This positive effect of restoration on sand accumulation was followed by an increase in gamma species richness and by an increase in vegetation conservation status at the alpha (i.e.…”
Section: Positive Effect Of Restoration On Geomorphology Typical Spec...supporting
confidence: 63%
“…As previously demonstrated elsewhere, we found that marram grass ( Ammophila arenaria ) plantation combined with trampling protection is a very efficient method allowing sand accretion and dune building (Lillis et al, 2004; Vestergaard, 2004; Grafals‐Soto, 2012). Although the global outcome was positive, we found that sand accumulation mainly occurred in the first 10 years following restoration, with discrepancies among sites during the last decade.…”
Section: Discussionmentioning
confidence: 61%
“…In the last decade, researchers have combined life form and floristic vegetation description methods to overcome difficulties in analyzing data in disturbed habitats. For example, Vestergaard [93] generated quadrat groups based on floristic data through TWINSPAN and then described the life-form spectra in each to investigate the relationship between plant diversity and artificial dune development processes. Although similar to our methodology, Vestergaard did not use this combined methodology to define habitat analogs for target plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Festuca sp. and Senecio vulgaris dominate stabilized dunes under low-nutrient conditions [69][70][71]. Other species rely on already-developed soil to establish a population, which is only provided at the groyne and control sites, e.g., Hypochaeris radicata [72], or developed dune landscapes with depressions and increased soil moisture, e.g., Juncus sp.…”
Section: Single Species Analysismentioning
confidence: 99%